First insights into infants' and children's aha-experiences: A parent report study - Haugen, Josefine; Prenevost, Mathilde H.; Nilsen, Ida B.R.; Reber, Rolf (Cognitive development, 2024)
This study provides first insights into aha-experiences in infancy and childhood. In two studies, a content analysis of parental reports from two different populations, a Norwegian sample and an international sample of English-speaking parents, was conducted. Parents described 606 aha-stories of their children (age 3 weeks to 16 years). Three main findings were replicated across two studies: (1) Even infants may have aha-experiences; (2) Children have aha-experiences on various topics related to action and cognition; (3) The focus of aha-experiences shifts from action to cognition with age (3 weeks-8 years, Odds Ratios > 1.567). These findings may have implications for understanding what motivates children's learning and cognitive development and for future research. [Display omitted] •Even infants may have aha-experiences.•Children have aha-experiences on various topics related to action and cognition.•The focus of children’s aha-experiences shifts from action to cognition with age.•Most aha-experiences in children yield positive affect.